'I saw it as a second chance': A qualitative exploration of experiences of treatment failure and regimen change among people living with HIV on second- and third-line antiretroviral therapy in Kenya, Malawi and Mozambique. Issue 8 (3rd August 2019) - Burns, Rose; Borges, Joana; Blasco, Philippe; Vandenbulcke, Alexandra; Mukui, Irene; Magalasi, Denview; Molfino, Lucas; Manuel, Rolanda; Schramm, Birgit; Wringe, Alison
ABSTRACT: Increasing numbers of people living with HIV (PLHIV) in sub-Saharan Africa are experiencing failure of first-line antiretroviral therapy and transitioning onto second-line regimens. However, there is a dearth of research on their treatment experiences. We conducted in-depth interviews with 43 PLHIV on second- or third-line antiretroviral therapy and 15 HIV health workers in Kenya, Malawi and Mozambique to explore patients' and health workers' perspectives on these transitions. Interviews were audio-recorded, transcribed and translated into English. Data were coded inductively and analysed thematically. In all settings, experiences of treatment failure and associated episodes of ill-health disrupted daily social and economic activities, and recalled earlier fears of dying from HIV. Transitioning onto more effective regimens often represented a second (or third) chance to (re-)engage with HIV care, with patients prioritising their health over other aspects of their lives. However, many patients struggled to maintain these transformations, particularly when faced with persistent social challenges to pill-taking, alongside the burden of more complex regimens and an inability to mobilise sufficient resources to accommodate change. Efforts to identify treatment failure and support regimen change must account for these patients' unique illness and treatment histories, and interventions should incorporate tailored counselling and social and economic support.